Gaps Between micronutrient Intake and prenatal Supplement formulations in Latin American women of childbearing age. - Yépez-Garcia, Martha Cecilia; Herrera-Cuenca, Marianella; Cortes-Sanabria, Lilia Yadira; Lorenzo, Jessica; Weiler, Mary; Gomez-Salas, Georgina; Kovalskys, Irina; Fisberg, Mauro; Pareja, Rossina; Rigotti, Attilio; Albuja, Daniel; Hernandez-Rivas, Pablo (Archivos Latinoamericanos de Nutrición)
Introduction: Supplementation with key nutrients has been an effective strategy to meet nutritional requirements, particularly when diets alone are insufficient to fulfill needs or correct existing deficiencies. However, micronutrient deficiencies among women of childbearing age in Latin America remain a significant public health challenge, especially during the preconception period, when nutritional status critically influences maternal and fetal outcomes. Objective: This study aimed to analyze the micronutrient composition of commonly prescribed prenatal supplements in countries participating in the ELANS and compare it with dietary intake among women of childbearing age to identify relevant nutritional gaps relevant. Materials and methods. Commonly prescribed prenatal supplements in the ELANS countries were analyzed and compared with previously reported dietary intake data. A population-level model was used to estimate total micronutrient intake under a supplementation scenario. Results. Significant micronutrient gaps were identified, particularly for calcium, vitamin D, vitamin E, and choline. Choline intake was markedly inadequate, and none of the evaluated supplements contained this nutrient. While supplementation improved coverage for some micronutrients, it also led to potentially excessive intake of others, including iron and several B-complex vitamins. Substantial variability in supplement composition was observed across countries Conclusions. These findings reveal a mismatch between prenatal supplement composition and population nutritional needs, characterized by the coexistence of deficiencies and potential excesses. Tailored, evidence-based supplementation strategies are needed to better align regional nutritional gaps.